Retinal involvement of coronavirus disease (COVID-19): A systematic review - Mohammad Eko Prayogo; Angela Nurini Agni (Journal of Community Empowerment for Health, 2021)
COVID-19 has wide-ranging manifestations which involve various organs. Although COVID-19 is known to affect mainly the respiratory system, many patients suffered from ocular manifestations following SARS-CoV-2 infection, especially conjunctivitis. However, there was some evidence of broader ocular involvement, which could involve the retinal layer. This review aims to analyze the possible explanation of retinal involvement in COVID-19 and whether comorbidities increase the risk of retinal involvement in COVID-19. We conducted a systematic literature search during September 2020 using the PUBMED database and other additional sources (e.g., Google Scholar). There was no year of publication nor language restriction. Six papers are used in this literature review: two studies reported retinal lesions in COVID-19 patients, one study detected SARS-CoV-2 RNA in retinal biopsies and three studies proposed possible mechanisms of retinal involvement in COVID-19. Ocular structures express ACE-2, such as the aqueous humor, pigmented epithelium, and retina. This is supported by the finding of SARS-CoV-2 nucleic acid in postmortem patients. Retinal involvement in COVID-19 patients includes hyperreflective retina lesions, subtle cotton wool spots, and microhemorrhage. However, these findings do not necessarily indicate the specificity of retinal involvement. Diabetes mellitus may be associated with disease severity in patients with COVID-19. Some evidence of retinal involvement in SARS-CoV-2 infection involves the detection of retinal lesions, the expression of ACE-2 in the retina, and the role of comorbidities.